Ethylene Scavenging Systems in Packaging of Fresh Produce: A Review. Issue 2 (17th February 2021) - Sadeghi, Kambiz; Lee, Younsuk; Seo, Jongchul
ABSTRACT: Ethylene biosynthesis from fresh produce could accelerate the ripening and reduce the postharvest life under conducive conditions. Ethylene scavenging systems, an active packaging, serve to prolong the shelf life of fresh produce and prevent deterioration caused by ethylene. This review provides an overview of ethylene scavenging mechanisms such as chemical oxidizing, ethylene receptor blocking, ethylene adsorption, and ethylene photocatalytic oxidizing. Particularly, the scope of this study is to develop a better understanding of the ethylene scavenging systems through discussing the scavenging mechanisms, scavenging materials, and preparation methods. In addition, ethylene biosynthesis pathway and effects of ethylene gas on the quality of fresh produces during storage were briefly discussed. Furthermore, recent progress, challenges, and future prospects were provided with a focus on the packaging of fresh produce.